Inhibition by rno-circRNA-013017 of the apoptosis of motor neurons in anterior horn and descending axonal degeneration in rats after traumatic spinal cord injury - Qin, Chuan; Liu, Yi; Xu, Pei-Pei; Zhang, Xin; Talifu, Zuliyaer; Liu, Jia-Yi; Jing, Ying-Li; Bai, Fan; Zhao, Li-Xi; Yu, Yan; Gao, Feng; Li, Jian-Jun (Frontiers in Neuroscience, 2022)
Spinal cord injury (SCI) often causes continuous neurological damage to clinical patients. Circular RNAs (circRNAs) are related to a lot of diseases, including SCI. We previously found five candidate circRNAs which were likely to regulate the secondary pathophysiological changes in rat model after traumatic SCI. In this study, we first selected and overexpressed target circRNA in rats. We then explored its functional roles using various functional assays in a rat model after SCI. As a result, we found that rno-circRNA-013017—the selected target circRNA—reduced neuron apoptosis, preserved the survival and activity of motor neurons, and regulated apoptosis-related proteins at 3 days post-SCI using western blot,immunofluorescence,polymerase chain reaction. Additionally, we found that rno-circRNA-013017 inhibited descending axonal degeneration and preserved motor neurons and descending axons at 6 weeks post-SCI using immunofluorescence, biotin dextran amine diffusion tensor imaging. Finally, the overexpression of rno-circRNA-013017 promoted the locomotor function of rats after SCI using open-field test and gait analysis. Focusing on the functions of rno-circRNA-013017, this study provides new options for future studies exploring therapeutic targets and molecular mechanisms for SCI.